2008
DOI: 10.1071/rd08024
|View full text |Cite
|
Sign up to set email alerts
|

Putative imprinted gene expression in uniparental bovine embryo models

Abstract: Abstract. Altered patterns of gene expression and the imprinted status of genes have a profound effect on cell physiology and can markedly alter embryonic and fetal development. Failure to maintain correct imprinting patterns can lead to abnormal growth and behavioural problems, or to early pregnancy loss. Recently, it has been reported that the Igf2R and Grb10 genes are biallelically expressed in sheep blastocysts, but monoallelically expressed at Day 21 of development. The present study investigated the impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…In addition, parthenotes and embryos could differ in terms of the stress signalling that triggers growth arrest and eventually apoptosis, p66 shc being preponderant in parthenotes over p53. The lower expression of CX43 in parthenotes does not correspond to morphological or functional differences between both blastocyst types within Day-8 embryos [7]. Lower expression of OCT3/4 in parthenotes may indicate low pluripotency in such blastocysts.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…In addition, parthenotes and embryos could differ in terms of the stress signalling that triggers growth arrest and eventually apoptosis, p66 shc being preponderant in parthenotes over p53. The lower expression of CX43 in parthenotes does not correspond to morphological or functional differences between both blastocyst types within Day-8 embryos [7]. Lower expression of OCT3/4 in parthenotes may indicate low pluripotency in such blastocysts.…”
mentioning
confidence: 75%
“…In cattle, production of reconstructed embryos by somatic cell nuclear transfer (SCNT) [5] and intracytoplasmic sperm injection (ICSI) [6] depends on successful oocyte activation. Therefore, procedures involving SCNT and ICSI could benefit from a better knowledge of mechanisms that differ between embryos and parthenotes.Contrary to the research in mice and humans, most studies have failed to detect putatively imprinted genes in bovine early development [7,8], suggesting that monoallelic expression may not develop until after Day 21 of development, as occurs in ovine species [9]. In fact, a recent study found imprinted expression of bovine Mest-1 in Day-21 but not Day-14 embryos, while 7 other putatively imprinted genes were shown to be not imprinted at the two stages analyzed [10].…”
mentioning
confidence: 79%
See 3 more Smart Citations